Efeito de diferentes agentes dessensibilizantes no controle da hipersensibilidade dentinária – Estudo clínico, randomizado e cego - Mertz, Tuane (2019)
To evaluate by means of a prospective, randomized and blind clinical study the efficiency of four desensitizing agents in the treatment of cervical dentin hypersensitivity for the period of 60 days and also the impact of the oral health condition on patients quality of life through a questionnaire applied at the beginning and at the end of treatment. Materials and methods: Twenty-two patients with 116 teeth with hypersensitivity were selected. They were randomized and divided into 4 groups (n = 29 teeth) according to the applied treatment: GD - Gluma Desensitizer; CV - Clinpro White Varnish; SB - Single Bond; AS - AdheSE. Sensitivity levels were evaluated by probing and air-jet application of the triple syringe and the response indicated by the Visual Analogue Scale (VAS). Measurements were performed before, immediately after the application of each material during the first session (TI), after completing 7 days (T7), 30 days (T30) and 60 days after the first application (T60). Data were submitted to the Kruskal-Wallis test (p <0.05) for intra and intergroup comparisons throughout the evaluation periods; the Wilcoxon test (significance level of 5%) was used to compare the quality of life questionnaire responses and to evaluate whether there was a decrease in sensitivity with sweet and / or acidic foods the McNemar test. Results: In the intragroup comparison, there was a statistically significant decrease (p <0.05) from the initial period for all other periods in all treatments. Regarding the intergroup comparison, a statistically significant difference (p <0.05) between the different desensitizing agents was observed only in the 7-day period for SB. Still, there was a significant decrease in discomfort when eating sweet and / or acidic foods and consequent improvement in patients' quality of life. Results: In the intragroup comparison, there was a statistically significant decrease (p <0.05) from the initial period for all other periods in all treatments. Regarding the intergroup comparison, a statistically significant difference (p <0.05) between the different desensitizing agents was observed only in the 7-day period for SB. Still, there was a significant decrease in discomfort when eating sweet and / or acidic foods and consequent improvement in patients' quality of life. Conclusion: This clinical study showed that the four desensitizing agents evaluated were effective in the treatment of dentin hypersensitivity. Clinical Relevance: Contribute to the treatment of dentin hypersensitivity by providing new data and treatment options for this painful condition.